STRATEGI PENINGKATAN UKM INDUSTRI SANITAIRUD. DARMO PUTRO UNTUK KELANGSUNGAN USAHA DI KOTA MALANG - Hendra Rustantono (Institut Pendidikan Tapanuli Selatan, 2021)
In its development, the sales condition of the sanitation industry is still relatively stagnant due to traditional marketing techniques, less varied products, and the lack of efforts from the government in supporting the development of the potential of the sanitation industry. This study aims to analyze the influence of the internal and external environment in the UD sanitary industry. Darmo Putro for business continuity in Malang City in order to improve business competition strategy. This study uses a qualitative approach with a descriptive type of research. The data studied include internal and external aspects, so that opportunities, constraints, strengths and weaknesses of the sanitation industry SMEs will be found in facing competitors. This research focuses on the strategy of increasing the sanitation industry SMEs for business continuity in terms of management, marketing, economic, market and competition, and social aspects. The results of this study indicate that based on a SWOT analysis of UD's internal and external factors. Darmo Putro, the recommended and appropriate alternative strategy is a combination of market penetration strategy and product development strategy. Where the market penetration strategy is to increase the market share of a product by increasing the sales force, increasing sales promotions and other promotional efforts. In product development strategy, UD. Darmo Putro will concentrate or focus on efforts to improve or modify products that have different concepts and are better than competitors and at competitive prices.